Analysis of formation methods of graphic competence of future engineering teachers - Koliasa, P. (Journal of Education, Health and Sport, 2022)
The article substantiates the need to improve the formation methods of graphic competence of future engineering teachers by means of digital technologies. To achieve the goal of the article the analysis of normative documents of training of future engineering teachers in the field of digital technologies, methods of teaching graphic disciplines in Higher Education Institutionі, prospects of improving graphic training of future engineering teachers by means of digital technologies are determined. Based on the analysis of work programs of the cycle of disciplines of graphic training, we conclude that today the method of formation of graphic competence in future engineering teachers in the field of digital technologies needs to be improved. It is established that the most effective way to reform the system of training future engineering teachers in the field of digital technologies is the use of modern learning technologies, which include design, research, integrative technologies that provide personality-oriented learning and graphic competence of future engineering teachers in the field digital technologies. It is determined that it is necessary to improve the teaching methods of the discipline "Engineering Computer Graphics", which will include the study of two-dimensional graphics, three-dimensional spatial modeling, 3D printing technologies and the creation of 4D objects in KOMPAS-3D.